Tow placement effects on fiber waviness and tensile performance of 3D-tow reinforced hybrid-molded composites. (1st May 2023) - Miller, Justin D.; Blanchard, Patrick; Dahl, Jeffery; Mansson, Jan-Anders E.
Abstract: Three-dimensional (3D) tow reinforced hybrid molding combines continuous fiber composite tow with injection overmolding to improve mechanical performance of molded components, but tensile performance is not accurately captured by conventional modeling processes. When wrapped around load introduction points, the fibers of a thick tow traverse a shorter distance at the inner radius than the outer radius leading to waviness on the inner region of each wrap. The Hsaio and Daniel model was used to predict local elastic properties of the wavy fiber composite and spatially varying material properties were applied to 3D finite element models of a suspension link. Neglecting fiber waviness overpredicted experimental tensile stiffness and strength by 36% and 33% respectively while modeling waviness overpredicted stiffness and strength by only 9% and 14% respectively. Tow wrap configuration, waviness propagation, and material parameters have significant effect on tensile performance while the tow has little effect on compressive performance.